2021
DOI: 10.1177/23969415211010419
|View full text |Cite|
|
Sign up to set email alerts
|

‘I have more control over my life’: A qualitative exploration of challenges, opportunities, and support needs among autistic university students

Abstract: Background Autistic people are known to experience more mental health issues than non-autistic people, and the same is true among university students. These difficulties can have long-term consequences, such as dropping out of university and unemployment. Understanding the challenges autistic students face can help institutions to better support this group, while allowing celebration of the opportunities higher education offers. Methods 12 autistic university students took part in semi-structured interviews ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 84 publications
1
17
0
Order By: Relevance
“…This finding mirrors Pellicano et al’s (2021) research with Australian autistic people and goes against the stereotyped view that autistic people lack social interest and our findings support counter-arguments to the theoretical proposal that autistic people lack social motivation ( Jaswal and Akhtar, 2018 ). University can offer many social opportunities for autistic people, and while they may face challenges within social environments ( Scott and Sedgewick, 2021 ), we must find ways to enable autistic students to flourish socially in pandemic-adapted universities. Particularly, making the social environment fit for the autistic student, rather than the other way round, is vital ( Vincent et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding mirrors Pellicano et al’s (2021) research with Australian autistic people and goes against the stereotyped view that autistic people lack social interest and our findings support counter-arguments to the theoretical proposal that autistic people lack social motivation ( Jaswal and Akhtar, 2018 ). University can offer many social opportunities for autistic people, and while they may face challenges within social environments ( Scott and Sedgewick, 2021 ), we must find ways to enable autistic students to flourish socially in pandemic-adapted universities. Particularly, making the social environment fit for the autistic student, rather than the other way round, is vital ( Vincent et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, societies, clubs, and university events (e.g., “Welcome Week”) should consider how they can be accessible to autistic students. This accessibility might be achieved by providing clear information in advance about social events, making sure events are in well-designed sensory spaces or using peer mentoring programs ( Cage et al, 2020 ; Scott and Sedgewick, 2021 ). Indeed, peer support programs for autistic students have shown promise ( Duerksen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of ensuring that autistic voices guide autism research and practice is increasingly recognized (Fletcher-Watson et al, 2019; Pellicano et al, 2018). Indeed, autistic students have suggested that autism trainings for university teaching staff should forefront the experiences of autistic people (Sarrett, 2018; Scott & Sedgewick, 2021). Fraser (2000) asserted that institutional inequalities in status, which situate some people as “normative” and others as “deficient,” can only be overcome through equal representation of those who have been disempowered (Vincent et al, 2022).…”
Section: Why Take a Participatory Approach To Autism Training?mentioning
confidence: 99%
“…Even some disability support staff lack autism understanding (Kim & Crowley, 2021). Autistic people and academic staff, including professors and administrators, report that university disability accommodations, which focus primarily on academic progress, often fail to adequately support autistic students in domains such as social connectedness, daily living, and mental health (Accardo et al, 2019; Anderson et al, 2017, 2018; Cai & Richdale, 2016; Sarrett, 2018; Scott & Sedgewick, 2021; Zeedyk et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation